Once walked with gods - Barclay, James autor (Elves (Gollancz), 2011)
Takaar is Lord of the Al-Arynaar, the hero of countless battles, defender of the faith for nearly two thousand years. But in the last battle his courage broke...<U+000d><U+000a>The elves have fouth to escape an ancient evil. The fight was brutal, the TaiGethen Warrior caste was all but wiped out, the Al-Arynaar reduced to remnants. But with nearly all having crossed the dimensions to safety in Calaius, the battle line breaks and a hundred thousand elves are left to their doom.<U+000d><U+000a>And elves remember when courage fails. Takaar is shunned and vilified and the anger of his people in matched only by his own shame. For an Elf who once walked with Gods perhaps the ultimate shame of taking his own life in only fitting...<U+000d><U+000a>But in Calaius the Elven nation is tearin itself apart. A thousand years of peace has allowed old rivalries to bi reborn and elves who once stood shoulder to shoulder now face each other across line of swords. Men from the North are fanning the flames. War is coming.<U+000d><U+000a>Auum, a TaiGethen warrior, believes there is one elf who can unite them again. And so begins a perilous quest to bring Takaar back from the forests, to unite elves against the true enemy: Mankind.